Influence of nitrogen deficiency on leaf anatomy, organelle quantities, and photosynthetic traits of the NAD-ME type C4 grass, Panicum miliaceum (common millet) - Harunobu Hisatomi; Osamu Ueno (Plant Production Science, 2025)
C4 plants perform photosynthesis by close coordination between mesophyll (M) and bundle sheath (BS) cells. Although the cellular responses of C4 plants to nitrogen (N) deficiency have been studied for several C4 grasses of NADP-malic enzyme type, those of other C4 decarboxylation types are not fully investigated. We examined structural and physiological responses in leaves of Panicum miliaceum, a C4 grass of NAD-malic enzyme type, to N deficiency. Plants were grown under four levels of N supply (0.05 to 1.2 g N per 5-L pot). With decreasing N supply level, photosynthetic rate decreased, whereas the activity of phosphoenolpyruvate carboxylase more greatly decreased than that of ribulose-1,5-bisphoshate carboxylase/oxygenase, and δ13C values increased. Photosynthetic N use efficiency increased with decreasing N level. The N level did not greatly affect the leaf thickness, interveinal distance, and sizes of M and BS cells. The quantities of chloroplasts and mitochondria tended to decrease in both cells of the low N plants. In particular, the BS mitochondria, the decarboxylation site of C4-acids, remarkably decreased. The number of thylakoids per granal stack in the M chloroplasts increased in the low N plants. The low-N plants had thicker cell walls in both M and BS cells. Meanwhile, the N level did not affect the density of plasmodesmata in the BS cells. This study characterized the response of leaves in P. miliaceum to N deficiency in detail, and suggests that the decreased BS mitochondria may be one of factors responsible for the decreased photosynthetic capacity.